Socio-Psychological Characteristics of Leaders Working in the Higher Education System - Khasanovich, Tilavov Mukhtor (International Journal on Integrated Education, 2023)
The article presents data from a scientific study of the personal characteristics of leaders of modern universities. The work uses psychological diagnostic methods using classical techniques used in the practice of domestic and foreign psychologists. As a result of the study, a comparative analysis of the personality of a modern leader was carried out in the context of the requirements of the educational standard.